"A Good Man Always Knows His Limitations": The Role of Overconfidence in Criminal Offending. (August 2013) - Loughran, Thomas A.; Paternoster, Raymond; Piquero, Alex R.; Fagan, Jeffrey
Objectives: This study examines the prevalence of overconfidence in the perceived risk of committing crime and whether such overconfidence is related to criminal behavior. Methods: Two samples were used—a sample of high school students who committed minor offenses and a sample of serious juvenile offenders most with felony arrests. Overconfidence in risk was estimated as the difference between the perceived risk of arrest for one's self and for a generalized other. The proportion of over- and underconfident persons were estimated in both samples, while pooled and random effects logit models were used to estimate the effect of risk on both self-reported offending and arrest within the sample of serious offenders. Results: A large proportion of youth were found to be overconfident with respect to their perceived risk, with a higher prevalence in the conventional high school sample. Within the sample of serious juvenile offenders, being overconfident about one's own risk was found to be related to both self-reported offending and arrest, net of a base rate measure of others' risk. Conclusions: We outline a theory of the relationship between overconfidence and crime that links overconfidence with a self-attribution bias and biased updating of perceived risk with new information.